1995
DOI: 10.1111/j.1464-410x.1995.tb00776.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of the hCG stimulation test in the endocrine evaluation of cryptorchidism

Abstract: The hCG test is a valid indicator of the presence of functioning testicular tissue. It is predictive of anorchia and a good response to hCG suggests the presence of testes sufficiently large for orchidopexy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Undetectable plasma anti-müllerian hormone levels, lack of plasma testosterone increase after hCG stimulation, and high plasma gonadotropin levels are, in our opinion and according to others, the most useful indicators in the evaluation of a patient with anorchia, and they can reliably predict bilateral anorchia in normal phenotypic male subjects. 4,17,[25][26][27] In our study, surgery and histological studies always confirmed the diagnosis of bilateral anorchia both in Group A and Group B patients. Although molecular defects have not yet been identified, 16,25,[28][29][30] familial cases of anorchia 1,6,10,11-13 and associated congenital malformations 2,14 have been previously reported suggesting that genetic and/or environmental factors may play an important role in the pathogenesis of anorchia.…”
Section: Discussionsupporting
confidence: 68%
“…Undetectable plasma anti-müllerian hormone levels, lack of plasma testosterone increase after hCG stimulation, and high plasma gonadotropin levels are, in our opinion and according to others, the most useful indicators in the evaluation of a patient with anorchia, and they can reliably predict bilateral anorchia in normal phenotypic male subjects. 4,17,[25][26][27] In our study, surgery and histological studies always confirmed the diagnosis of bilateral anorchia both in Group A and Group B patients. Although molecular defects have not yet been identified, 16,25,[28][29][30] familial cases of anorchia 1,6,10,11-13 and associated congenital malformations 2,14 have been previously reported suggesting that genetic and/or environmental factors may play an important role in the pathogenesis of anorchia.…”
Section: Discussionsupporting
confidence: 68%
“…Inhibin B and AMH levels are elevated in AIS (61), with the latter correlating with the functioning testicular tissue amount. A short-term hCG stimulation test can be performed, and androgen levels in the blood are measured before and after stimulation (62).…”
Section: Androgen Insensitivity Syndromementioning
confidence: 99%
“…The neonatal gonad is more active than at any time in childhood until puberty, reaching a peak at about a 6-8 weeks of age. A balance needs to be reached between performing the hCG test when the gonad is normally most active (testosterone secretion normally rises in the fourth week of life, peaking at 1-3 months [6][7][8] ) and proceeding with the investigations as promptly as possible. While some would advocate that this test is deferred beyond 2 weeks of age, this may not be necessary.…”
Section: Determination Of Internal Anatomymentioning
confidence: 99%